2010 IEEE Second International Conference on Social Computing 2010
DOI: 10.1109/socialcom.2010.99
|View full text |Cite
|
Sign up to set email alerts
|

GDC: Group Discovery Using Co-location Traces

Abstract: Abstract-Smart phones can collect and share Bluetooth co-location traces to identify ad hoc or semi-permanent social groups. This information, known to group members but otherwise unavailable, can be leveraged in applications and protocols, such as recommender systems or delay-tolerant forwarding in ad hoc networks, to enhance the user experience. Group discovery using Bluetooth co-location is practical because: (i) Bluetooth is embedded in nearly every phone and has low battery consumption, (ii) the short wir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…The overall complexity of Algorithm 1 is O(KLT ) where K is the number of sampling iterations (we set K = 100 in our experiments). Compared to previous works [38,25] for which the complexity grows superlinearly (quadratically or sometimes exponentially) with the problem size, GroupUs scales well with the number of links and the number of interaction types, and hence it can learn from large-scale data in linear time.…”
Section: Inference and Parameter Estimationmentioning
confidence: 95%
See 1 more Smart Citation
“…The overall complexity of Algorithm 1 is O(KLT ) where K is the number of sampling iterations (we set K = 100 in our experiments). Compared to previous works [38,25] for which the complexity grows superlinearly (quadratically or sometimes exponentially) with the problem size, GroupUs scales well with the number of links and the number of interaction types, and hence it can learn from large-scale data in linear time.…”
Section: Inference and Parameter Estimationmentioning
confidence: 95%
“…Eagle et al [10] analyed a network constructed from BT links and phone call logs to identify friendship networks. Mardenfeld et al [25] also studied a BT network to discover groups. Other works have relied on other mobile sensors, like infrared, and microphones, to address the limitations of Bluetooth to detect real face-to-face proximity, rather than just detecting people sharing an office or a large space [15,40,30].…”
Section: Related Workmentioning
confidence: 99%
“…With this in mind we designed a new algorithm, Group Discovery using Co-location Traces (GDC) [8]. It uses copresence traces to identify groups.…”
Section: A Backgroundmentioning
confidence: 99%
“…The use of such validation techniques is demonstrated by Mardenfeld, et al [8], where an after-study survey revealed the GDC algorithm finds measurably better groups than another popular community detection algorithm, KClique. This survey does not help evaluate alternative group detection algorithms, illustrating the need for some other way to evaluate these results.…”
Section: Introductionmentioning
confidence: 99%
“…Crowdsensing permits a huge number of sensing devices that share the collected data by the purpose to enumerate a phenomena of mutual interest [1]. Mobile devices are equipped with different sensors such as camera, GPS, digital compass, microphone, light sensor, accelerometer, and bluetooth as proximity sensor [2]. Crowdsensing empowers a large amount of mobile phones to be utilized for trading data among their clients, as well as for activities which might have an enormous societal impact.…”
Section: Introductionmentioning
confidence: 99%